2015
DOI: 10.3892/ol.2015.3274
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of B7-H3 and TLT-2 in human oral squamous cell carcinoma

Abstract: Abstract. The aim of the present study was to investigate the role of immune regulatory molecules B7-H3 [also known as cluster of differentiation 276] and triggering receptor expressed on myeloid cell-like transcript-2 (TLT-2) in patients with oral squamous cell carcinoma (OSCC). Human OSCC samples were obtained from 76 patients (female, 32; male, 44; age range, 23-81 years; median age, 50.9 years) that underwent resection for OSCC at Peking University Shenzhen Hospital (Shenzhen, China) between 2007 and 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The rapid‐fire clinical successes from blocking the ligands of B7 superfamily, such as CTLA‐4 and PD‐1, have opened prospects for extending this potential cancer immunotherapy by inhibiting more recently discovered checkpoint ligands and receptors . B7‐H3, a newly identified member of the B7 family of molecules, has been linked to head and neck cancer, and its overexpression has been correlated with poor survival . Consistent with those reports, our immunohistochemical staining indeed indicates overexpression of B7‐H3 in the HNSCC tissues as compared with oral mucosa or the dysplasia.…”
Section: Discussionsupporting
confidence: 88%
“…The rapid‐fire clinical successes from blocking the ligands of B7 superfamily, such as CTLA‐4 and PD‐1, have opened prospects for extending this potential cancer immunotherapy by inhibiting more recently discovered checkpoint ligands and receptors . B7‐H3, a newly identified member of the B7 family of molecules, has been linked to head and neck cancer, and its overexpression has been correlated with poor survival . Consistent with those reports, our immunohistochemical staining indeed indicates overexpression of B7‐H3 in the HNSCC tissues as compared with oral mucosa or the dysplasia.…”
Section: Discussionsupporting
confidence: 88%
“…B7-H3 is one of the negative costimulatory molecules in the B7 family, and its abnormal expression disrupts the balance of T cell immune response, thus mediating tumor immune escape. Numerous studies have shown that B7-H3 protein is abnormally high expressed in colorectal cancer [15] , prostate cancer [16] , pancreatic cancer [17] , squamous cell carcinoma [18] , non-small cell lung cancer [19] , gastric cancer [20,21] and other tumors, and its expression has significant clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the receptor of B7-H3 is currently unknown. Some researchers have proposed that the triggering receptor expressed on myeloid cell (TREM)-like transcript 2 (TLT-2) may be a putative counter receptor for B7-H3 ( 34 , 35 ). Therefore, further studies are advocated to identify the receptor of B7-H3, and elucidate the signaling mechanism of B7-H3.…”
Section: Discussionmentioning
confidence: 99%